Factors Affecting The Low Interest Of Vasectomy Acceptors In Sigumpar Village Sigumpar District, Toba Regency Year 2021 - Erita Saragih (Institute of Computer Science (IOCS), 2021)
There are various choices of contraceptives, one of which is male contraception, namely vasectomy contraception. A vasectomy is an act of blocking or blocking the way for sperm through surgical means to prevent fertilization. This study aims to describe the factors that influence the low interest of vasectomy acceptors in Sigumpar Village, Sigumpar District. This research was conducted from April to May 2021 using a descriptive research design. The number of samples in this study were 139 people. Sampling was done by using purposive sampling technique. The results showed that the majority of respondents were <45 years old (73.4%), had high school education (64.0%), earned Rp. 850,000-Rp. 1,000,000 (64.7%), ethnic Batak (100%), Muslim (90.6%), have sufficient knowledge about Vasectomy (43.2%), stated, have a positive attitude towards Vasectomy (78.4%), and were not given support by family planning officers to use Vasectomy (54.7% ). For educational institutions, it is hoped that the results of this study can be additional information related to the factors that influence the low interest of vasectomy acceptors that contribute to maternity courses. For health workers, it is hoped that they can provide complete information about Vasectomy including negative rumors or myths about Vasectomy to family planning participants so that they have good knowledge and attitudes towards Vasectomy and are willing to use Vasectomy as an effective and efficient long-term contraceptive. For further research, it is recommended that further research be conducted on the analysis of factors that influence the low interest of vasectomy acceptors and it is necessary to consider the use of interview techniques in data collection so that the data obtained is more accurate.